In vitro fertilization - Elder, Kay, 1946- (Cambridge University Press, 2000)
This comprehensively updated and expanded second edition builds on its successful and popular predecessor, retaining the practical features which made the first edition such an essential guide to IVF. The edition describes additions to the range of ART clinical treatments, including the use of testicular and epididymal sperm, blastocyst stage transfer, and new perspectives in cryobiology and cryopreservation techniques. By incorporating laboratory techniques and protocols, with an even greater emphasis on quality control, it provides an indispensable and practical account. The introductory chapters covering the scientific background that underpins effective laboratory practice have been substantially expanded, derived from research in mammalian systems into the molecular biology of oogenesis, oocyte maturation, and early embryo metabolism. This second edition distils a wealth of practical and scientific detail for the benefit of all IVF practitioners.